Major Trends and Policies in Pakistan’s Energy Sector Management - Asia Mukhtar; Iram Khaild (Journal of Political Studies, 2017)
Energy sector in Pakistan is facing disastrous decline from almost one decade. There are multiple reasons behind this phenomenon. In order to find out genuine causes of this decline and workable solution it is dire need to hold a comprehensive study of three aspects of energy sector; energy generation, energy management and issues and problems in overall energy sector. The underlying purpose of this article is to bring out not only the causes of energy sector’s dilapidation but also suggest some workable solutions as well.